2011
DOI: 10.1038/modpathol.2010.218
|View full text |Cite
|
Sign up to set email alerts
|

Expression of claudin-4 (CLDN4) mRNA in intraductal papillary mucinous neoplasms of the pancreas

Abstract: Claudin-4, encoding a protein for tight junction formation and function, is highly overexpressed in pancreatic ductal adenocarcinoma and is also associated with invasive adenocarcinomas arising in intraductal papillary mucinous neoplasms of the pancreas. However, the expression pattern of claudin-4 during neoplastic progression of intraductal papillary mucinous neoplasms remains unknown. Using quantitative real-time reverse transcription-PCR, we analyzed claudin-4 mRNA in a panel of 14 pancreatic cancer cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“… 91 Consistent with these in vitro findings is a report that claudin-4 expression in pancreatic intraductal papillary mucinous neoplasms was associated with a more invasive phenotype. 92 Similarly, expression of claudin-3 and -4 was observed in advanced ovarian cancer but not in ovarian cystadenomas. 93 , 94 It has been reported, however, that re-expression of claudin-1 in breast cancer cells can lead to the increased apoptosis in three-dimensional cultures.…”
Section: Role Of Claudins and Tight Junctions In Cancermentioning
confidence: 96%
“… 91 Consistent with these in vitro findings is a report that claudin-4 expression in pancreatic intraductal papillary mucinous neoplasms was associated with a more invasive phenotype. 92 Similarly, expression of claudin-3 and -4 was observed in advanced ovarian cancer but not in ovarian cystadenomas. 93 , 94 It has been reported, however, that re-expression of claudin-1 in breast cancer cells can lead to the increased apoptosis in three-dimensional cultures.…”
Section: Role Of Claudins and Tight Junctions In Cancermentioning
confidence: 96%
“…Several studies have suggested that different clinical characteristics and distinct pathways to malignant progression exist among the various IPMN subtypes. Genetic alteration such as mutational status of GNAS or KRAS [ 42 44 ], as well as expression pattern of mucin [ 42 , 43 , 45 , 46 ] have been investigated. Recent meta-analysis suggested that subtype identification should be considered in future guidelines for management of IPMN, since subtypes have an impact on disease prognosis [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…39 Briefly, FFPE samples were cut into 10-Hm sections. One section was stained with hematoxylin-eosin for histological examination, and the number of sections needed for miR extraction was determined according to the estimated area of the neoplastic cells on hematoxylin-eosin staining.…”
Section: Macrodissection and Mir Extraction From Ffpe Samplesmentioning
confidence: 99%